Norms on Quotient Spaces of The 2-Inner Product Space - Harmanus Batkunde (Universitas Airlangga, 2021)
This paper discussed about construction of some quotients spaces of the 2-inner product spaces. On those quotient spaces, we defined an inner product with respect to a linear independent set. These inner products was derived from the -inner product. We then defined a norm which induced by the inner product in these quotient spaces.